2010
DOI: 10.1111/j.1365-2028.2009.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Germination responses of Spartidium saharae (Coss. & Dur.) Pomel (Fabaceae) to temperature and salinity

Abstract: Spartidium saharae is an endemic species of the Saharo-Arabian region. It is a tall shrub widely distributed in many sandy habitats including desert dunes and sandy systems in south-western part of Tunisia, where water and salinity are serious constraints. Laboratory experiments were carried out to assess temperature and salinity effects on seed germination. The seed germination responses were determined in complete darkness over a wide range of temperatures and salinities. Germination was inhibited by either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…High salinity reduces germination, seedling emergence, and ultimately crop establishment (Stumpf et al 1986;Fowler 1991;Khan and Ungar 1999;Puppala et al 1999;Ashraf 2001;Qasim et al 2003;Ashraf and Foolad 2005;Guma et al 2010;Jamila et al 2010;Zivdar et al 2011). Ahamad et al (2012) reported salinity stress significantly affected the rate of germination, root and shoot growth of four canola cultivars, while Long et al (2015) reported that root growth of canola is affected by salinity stress as early as 12 h post-exposure.…”
Section: Salinity (Ec Sol )mentioning
confidence: 99%
See 1 more Smart Citation
“…High salinity reduces germination, seedling emergence, and ultimately crop establishment (Stumpf et al 1986;Fowler 1991;Khan and Ungar 1999;Puppala et al 1999;Ashraf 2001;Qasim et al 2003;Ashraf and Foolad 2005;Guma et al 2010;Jamila et al 2010;Zivdar et al 2011). Ahamad et al (2012) reported salinity stress significantly affected the rate of germination, root and shoot growth of four canola cultivars, while Long et al (2015) reported that root growth of canola is affected by salinity stress as early as 12 h post-exposure.…”
Section: Salinity (Ec Sol )mentioning
confidence: 99%
“…Generally, germination and seedling vigor are considered to be highly sensitive to saline conditions, which lead to a considerable reduction of yield and biomass production (Hamdy et al 1993). Indeed, salt stress reduces germination and establishment of seedlings in many plant species (Fowler 1991;Khan and Ungar 1999;Guma et al 2010;Jamila et al 2010;Zivdar et al 2011), including B. napus (Puppala et al 1999;Ashraf 2001;Qasim et al 2003). Brassica napus seed germination decreases sharply under salinity stress, from 87% at 0 dS m −1 to 0.8% at 26 dSm −1 (Puppala et al 1999).…”
Section: Introductionmentioning
confidence: 99%